2023
DOI: 10.3846/jeelm.2023.17410
|View full text |Cite
|
Sign up to set email alerts
|

Diminution of Air Pollution From Nox and Smoke/Soot Emitted From Alcohols/Diesel Blends in Diesel Engine and Influence of the Exhaust Gas Recirculation (Egr)

Abstract: In this study, the impact of butanol-diesel blends and exhaust gas recirculation (EGR) on engine performance, NOX emissions, smoke, and particulate matter (PM) characteristics were experimentally investigated under fuel post-injection condition. The maximum peak of cylinder pressure is achieved under without EGR compared with applied different rates of EGR. Furthermore, the brake thermal efficiency (BTE) increased during the combustion of B20 and B10 by 4.25% and 2.61%, respectively, compared with diesel fuel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Experimental results show that incorporating ZnO NPs into BD greatly decreases NOx emissions. The fundamental mechanism involves ZnO NPs' catalytic characteristics, which improve the combustion process, resulting in improved combustion as well as lower peak temperatures inside the cylinder [66,67]. As a result, NOx emissions are lowered.…”
Section: Oxides Of Nitrogenmentioning
confidence: 99%
“…Experimental results show that incorporating ZnO NPs into BD greatly decreases NOx emissions. The fundamental mechanism involves ZnO NPs' catalytic characteristics, which improve the combustion process, resulting in improved combustion as well as lower peak temperatures inside the cylinder [66,67]. As a result, NOx emissions are lowered.…”
Section: Oxides Of Nitrogenmentioning
confidence: 99%
“…Waste fires contribute to air pollution by releasing a variety of dangerous chemicals into the environment, including dioxins, particulate matter, toxic materials, and furans [35]. There has not been much discussion of the importance of numerous garbage burnings as a local or global cause of air pollution [36].…”
Section: Air Pollutionmentioning
confidence: 99%
“…Ramesh et al 10 investigated the effect of injection timing on NOx emissions from a diesel engine, which showed that the retarded main injection timing, along with pilot and post, significantly reduced NOx emissions without compromising power output and thermal efficiency. Fayad et al 11 attempted to study the effect of EGR on NOx emissions from diesel engines using different types of fuels and concluded that the use of different rates of EGR reduced the maximum peak cylinder pressure as compared to no EGR, and that the use of 30% EGR reduced NOx emissions for all fuels as compared to 15% EGR. In addition, the bench calibration is only the basis, and ultimately, the vehicle emissions will prevail.…”
Section: Introductionmentioning
confidence: 99%